Monitoring and Surveillance of Veterinary Antimicrobial Use and Antibiotic Resistance in Animals - Firth, Clair L. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Antimicrobial resistance is a global One Health topic that affects us all, whether we are working in human or veterinary medicine. Although antibiotic use in farm animals is decreasing in many countries, other nations are still using these essential medical resources as growth promoters to boost economic gains. As veterinarians responsible for animal welfare, it is vital that we are permitted to treat sick animals effectively, but we must learn to be more prudent in our use of these drugs. It is essential that we, as responsible clinicians, policy makers, and researchers, develop methods of quantifying, monitoring, benchmarking, and reporting antibiotic use in both farm and companion animals, so that antimicrobial stewardship schemes can be implemented and their successes or failures analyzed. This Special Issue includes research on antibiotic use and resistance in a variety of animal species, covering cattle, sheep, pigs, poultry, and pets. The relationship between antimicrobial use and resistance in animals is investigated on a global scale, with authors from Austria, Australia, Brazil, Germany, Italy, India, the Netherlands, Peru, Portugal, Slovenia, and the United Kingdom.